The First Generation Theory of Fiscal Federalism: How Does It Affect Regional Governance? - Werang, Nicolaus Petrus Likuwatan; Werang, Maria Lusiana Florentin (Future Science, 2025)
The First Generation Theory (FGT) approach in fiscal federalism plays a significant role in explaining how central government funding interventions should drive fiscal independence, dependence and effectiveness at the sub-national government level. This study explicitly stresses the budgetary performance of the Tarakan region to assess the level of fiscal autonomy, dependence, and effectiveness from 2011 to 2025. Then, this study adopts a quantitative descriptive approach and content analysis, where the findings are fiscal performance through three leading indicators: AFI ratio (≤0.53) indicating the status of “Towards Independence”, AFD ratio of 71.90% which as “Very High”, and AFE of 82.20% which as “Less Effective”. The research findings justify that the Tarakan region is still very dependent on fund transfers from the central government, has a weak ability to mobilise Regional Income (PAD), and has not consistently achieved the planned revenue targets. The final implication of this study is to inform local governments to strengthen their fiscal space by elevating the capacity of the regional revenue system and adopting accountable financial planning in proportion to local needs.